TRIZ based computer aided LCA for Ecodesign. Issue 6 (1st November 2016) - Russo, Davide; Serafini, Marco; Rizzi, Caterina
ABSTRACT: With the growing environmental conscience, the focus of sustainability has shifted from environmental assessment to improvement. An increasing number of improvement tools are being developed, but they all lack integration with the assessment phase, or provide very simplified and unreliable assessment tools. We propose an integrated approach to environmental assessment and improvement, with a focus on green product development and problem solving. The main novelty of this work lies in the adoption of TRIZ (Theory of Inventive Problem Solving) fundamentals, which allow us to transform traditional LCA criticalities, i.e. the most impacting flows of a product, into eco improvement criticalities, i.e. the potential of improvement of each flow. For this, we developed a graphical ontology that guides the designer in mapping the product life cycle, identifying and highlighting criticalities, and tracking the improvement effort. A new approach is proposed, focused toward problem solving rather than environmental certification. Indeed, available systems fail to highlight the contradictions that normally occur during problem solving, in which any improvement is met with a trade-off that is never fully understood until a new assessment is performed. In the proposed methodology, the mapping scheme is designed to help problem solving, by graphically highlighting the critical product components that need to be improved, suggesting customized guidelines that target specific flows and life cycle phases, and foreseeing possible trade-offs that may arise. GRAPHICAL ABSTRACT: